Efficient dynamic nuclear polarization at high magnetic fields. - Morley, G; van Tol, J; Ardavan, A; Porfyrakis, K; Zhang, J; Briggs, G (2007)
By applying a new technique for dynamic nuclear polarization involving simultaneous excitation of electronic and nuclear transitions, we have enhanced the nuclear polarization of the nitrogen nuclei in 15N@C60 by a factor of 10(3) at a fixed temperature of 3 K and a magnetic field of 8.6 T, more than twice the maximum enhancement reported to date. This methodology will allow the initialization of the nuclear qubit in schemes exploiting N@C60 molecules as components of a quantum information processing device.